«Eastern Partnership» after the Vilnius Summit - A. Chernova (Vestnik MGIMO-Universiteta)
The third summit of EU's Eastern Partnership held in Vilnius in November 2013 became a real turning point in the development of this organization. And it didn't happen due to signing of the first EU Association Agreement of its kind with the partner states but due to a sudden turn of the largest and most important of them - Ukraine - to the Russia's rival integration project. By doing so Ukraine at least temporarily joined two of the other participating countries: Armenia and Belarus, the latter of which is already in the Custom Union. At the other pole of the Eastern Partnership there are Georgia and Moldavia which initialed the Association and Free Trade agreements with the EU in Vilnius. This widening gap within the Eastern Partnership attracted everybody's attention to the EU - Russia rivalry in the post-Soviet countries which is increasingly interpreted in terms of the clash of civilizations. In this article we'd rather touch upon some of the peculiarities of the Eastern Partnership itself and its participating countries which to a large extent predetermined such an outcome. Among them is the ambiguous legacy of the European Neighbourhood Policy, lack of membership perspective in the EU as well as the nature of societies and elites in these post-Soviet states.